Pedagogical Implementation and Professional Competence of Teachers in Preparing Curriculum-Based Learning Tools 2013 - Nurhayati, Nurhayati; Ahmad, Syarwani; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2024)
This research aims to analyze the pedagogical competence and professional competence of teachers, inhibiting factors, and evaluation of the preparation of K–13 curriculum-based learning tools at Banyuasin 13 public elementary schools. This research was conducted at SDN 13 Banyuasin, South Sumatra using qualitative research methods. Data collection techniques include Participatory Observation, Interviews, and Documentation. The results of this research are that teachers at SD Negeri 13 Banyuasin I effectively teach students by responding to material, answering questions, and applying pedagogical competencies. They improve learning conditions, help students excel, and provide correction. The 2013 Reform Curriculum faces challenges in teaching materials, methods, and competencies. The curriculum aims to develop students’ character, skills, and national unity, with an emphasis on teacher creativity and the role of school leaders. Improvements can be made by involving teachers in activities and workshops. Evaluation of internal processes and K-13 learning tools is used for educational planning and tool preparation.